WAYFINDING: FERRAMENTA DE PROJETOS NA GESTÃO HOSPITALAR - Bara, Guilherme Gattas; Abdalla, José Gustavo Francis; Rangel, Márcia Moreira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This study provides a discussion of the wayfinding in hospitals, once might interfere in how people move around. It is noteworthy that architecture added in behaviours in the humanization of institutions and in users cognition. The main goal of this study is to analyze wayfinding as a design´s tool for the visual communication in the hospital´s project. It is justified by the contribution that can offer while allows to benefit the spatial orientation for the best environmental comfort of the internal and external community of the hospital. It can also contribute to the regulation of flows and the processes of these flows guaranteed of the management agents of the institution.